Central America [in State of the Climate in 2017] - Alfaro Martínez, Eric J. (2018)
For this region, nine stations from five countries were analyzed. Stations on the Caribbean slope are: Philip Goldson International Airport, Belize; Puerto Barrios, Guatemala; Puerto Lempira, Honduras; and Puerto Limón, Costa Rica. Stations located on the Pacific slope are: Tocumen International Airport and David, Panamá; Liberia, Costa Rica; Choluteca, Honduras; and Puerto San José, Guatemala.